Martin Harold Phillips Bott. 12 July 1926—20 October 2018. (10th December 2019) - Watts, Anthony Brian
Abstract : Martin Bott was a geophysicist who made fundamental contributions to our understanding of gravity and magnetic anomalies and their geological interpretation. His research on the deep structure of the Earth's crust was both pioneering and innovative, and he showed how field geophysical measurements could be used to address geological problems such as the mechanics of granite emplacement, sedimentary basin formation and mountain building. When he began his research, the use of gravity and magnetic anomalies to understand deep crustal structure was in its infancy and largely confined to research laboratories in the oil and gas industry. Four decades later his lifetime efforts have seen the emergence of potential field methods as one of the principal means of constraining the structure, stress state and long-term strength of the Earth's crust and upper mantle in continents and oceans. Martin was an inspiring undergraduate teacher and outstanding supervisor, as reflected by his many research students who went on to prominent leadership positions in academia, government and industry. He leaves a legacy of more than 150 scientific papers in peer-reviewed journals and a lucidly written and beautifully illustrated textbook. As well as his many scientific achievements, Martin was an accomplished mountaineer, a dedicated churchgoer and an avid gardener. He saw no conflict between his science and his enduring Christian faith.